PENGARUH POLA ASUH ORANG TUA DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA SD KELAS V DI SD NEGERI MUARA BOLAK 4 KEC. SOSORGADONG. - REGINA SIPAYUNG (JURNAL ILMIAH MAKSITEK, 2018)
This research is a kind of quantitative research with correlation technique. Correlation techniques are used to test the hypothesis to find the relationship between two variables. Population in this research is all elementary school student of Class V in Elementary School of Muara Bolak 4 Kec. Sosorgadong as many as 60 students. This study is a population study. So that all students of class V become respondents. Data collection using questionnaires or questionnaires to find out the pattern of parent care and student discipline, while the method of observation and documentation used for data collection in the form of a list of students and the picture of Elementary School Grade V in Elementary School Muara Bolak 4 Kec. Sosorgadong. Research data that has been collected and then analyzed by using statistical analysis techniques, Testing research hypothesis using product moment formula. The results showed that the parenting pattern of elementary school students in grade V SD Muara Bolak 4 Kec. Sosorgadong with an average score of 70.11 included into the category "good enough" that is at intervals 66 - 72. While the level of discipline students of Elementary School Grade V in Elementary School Muara Bolak 4 Kec. Sosorgadong with an average value of 49.71 is also included into the category "good enough" that is at intervals 47-52. The results of hypothesis analysis using product moment correlation analysis showed that the value of rxy = 0.596 is in a positive direction. Relationship pattern of parent care with the level of discipline of students Elementary School Grade V in Elementary School Muara Bolak 4 Kec. Sosorgadong is included in the "strong enough" category with intervals of 0.40 - 0.599. The research data also shows that thitung = 5,651, while ttabel at significance level 5% = 1,671 and table at significant level 1% = 2,390. This means that thitung is larger than ttable. So it can be concluded there is a significant relationship between parenting parenting with the level of discipline Students Elementary School Class V in Elementary School Muara Bolak 4 Kec. Sosorgadong